Transfer of Metal Thin Films by Laser Induced Forward Technique - Hadi, Iman H (Al-Nahrain Journal of Science, 2018)
In this work preparation and characterization of Aluminum thin films by laser induced forward transfer has been studied. These thin films were deposited by thermal evaporation on glass substrates as donor substrates. These thin films were irradiated by a single pulse and transferred to a silver (Ag) and silicon (Si) receiver substrates. The laser source used for LIFT process was a Nd-YAG Q-Switching second harmonic generation (SHG) Pulsed Laser with a wavelength 532nm, repetition rate 1-6 Hz ,and pulse duration 10ns. Deposited size, morphology and adhesion to the receiver substrate as a function of the applied laser fluence are investigated.